2023
DOI: 10.3389/fendo.2023.1121900
|View full text |Cite
|
Sign up to set email alerts
|

Circulating liver function markers and the risk of COPD in the UK Biobank

Abstract: ObjectiveTo investigate the associations of circulating liver function marker levels with the risk of chronic obstructive pulmonary disease (COPD).MethodsWe leveraged the data of 372,056 participants from the UK Biobank between 2006 and 2010. The assessed circulating liver function markers included alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), total bilirubin (TBIL), albumin (ALB), and total protein (TP). Incident COPD was identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
3
5
0
Order By: Relevance
“…Specifically, low lung function that disrupts the exchange of oxygen and carbon dioxide could engender both conditions [ 38 ], causing metabolic dysregulation in brain cells and ultimately triggering depressive symptoms [ 39 ]. Moreover, the increased risk of depression ascribed to impaired lung function might be partially explained by the deterioration in the liver and renal functions, in line with prior studies [ 13 , 14 , 40 , 41 ]. For instance, a cohort study involving more than 370,000 participants revealed a significant association between liver function markers, such as ALT, TBIL, ALB, TP, GGT, and ALP, and an elevated risk of lung disease [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Specifically, low lung function that disrupts the exchange of oxygen and carbon dioxide could engender both conditions [ 38 ], causing metabolic dysregulation in brain cells and ultimately triggering depressive symptoms [ 39 ]. Moreover, the increased risk of depression ascribed to impaired lung function might be partially explained by the deterioration in the liver and renal functions, in line with prior studies [ 13 , 14 , 40 , 41 ]. For instance, a cohort study involving more than 370,000 participants revealed a significant association between liver function markers, such as ALT, TBIL, ALB, TP, GGT, and ALP, and an elevated risk of lung disease [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the increased risk of depression ascribed to impaired lung function might be partially explained by the deterioration in the liver and renal functions, in line with prior studies [ 13 , 14 , 40 , 41 ]. For instance, a cohort study involving more than 370,000 participants revealed a significant association between liver function markers, such as ALT, TBIL, ALB, TP, GGT, and ALP, and an elevated risk of lung disease [ 13 ]. Also, a MR study supported a causal relationship between lung diseases and renal function [ 14 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although chronic liver injury patients are usually asymptomatic, the liver enzymes appear generally significantly higher (7). In recent decades, several studies have indicated that liver enzyme disorders are associated with various diseases, such as chronic obstructive pulmonary disease (8), metabolic diseases (9), cardiovascular disease (10), and type 2 diabetes mellitus (T2DM) (11). Meanwhile, liver enzyme disorders are a significant predictive factors for increased patient mortality (12).…”
Section: Introductionmentioning
confidence: 99%